Spatial and Temporal Variation of Cultivable Communities of Co-occurring Endophytes and Pathogens in Wheat - Comby, Morgane; Lacoste, Sandrine; Baillieul, Fabienne; Profizi, Camille; Dupont, Joëlle (Frontiers in Microbiology, 2016)
The aim of this work was to investigate the diversity of endogenous microbes from wheat (Triticum aestivum) and to study the structure of its microbial communities, with the ultimate goal to provide candidate strains for future evaluation as potential biological control agents against wheat diseases. We sampled plants from two wheat cultivars, Apache and Caphorn, showing different levels of susceptibility to Fusarium head blight, a major disease of wheat, and tested for variation in microbial diversity and assemblages depending on the host cultivar, host organ (aerial organs versus roots) or host maturity. Fungi and bacteria were isolated using a culture dependent method. Isolates were identified using ribosomal DNA sequencing and we used diversity analysis to study the community composition of microorganisms over space and time. Results indicate great species diversity in wheat, with endophytes and pathogens co-occurring inside plant tissues. Significant differences in microbial communities were observed according to host maturity and host organs but we did not find clear differences between host cultivars. Some species isolated have not yet been reported as wheat endophytes and among all species recovered some might be good candidates as biological control agents, given their known effects towards plant pathogens.